Planning and Establishing On-Farm Field Trials - Marcelo Wallau; Esteban Rios; Ann Blount (EDIS, 2021)
Planning and preparation can increase chances of successful outcomes from demonstration plots. This 5-page publication focuses on guiding the successful establishment of demonstration trials and is targeted to county, regional, and state specialized Extension faculty who aim to develop on-farm research and demonstration sites as part of their programs. Written by Marcelo Wallau, Esteban Rios, and Ann Blount, and published by the UF/IFAS Agronomy Department, January 2021.